Handbook of ecological indicators for assessment of ecosystem health - Jnsen, Sven Erik, 1934-; Xu, Fu-Liu.; Costanza, Robert (Boca Raton, FL : CRC Press, 2010)
'Continuing in the tradition of its bestselling predecessor, the Handbook of Ecological Indicators for Assessment of Ecosystem Health, Second Edition brings together world-class editors and contributors who have been at the forefront of ecosystem health assessment research for decades, to provide a sound approach to environmental management and sustainable development. Significantly updated and expanded, this authoritative resource details a proven framework for selecting, evaluating, and validating ecological indicators for ecosystem health assessment. It guides readers through the application of this framework to a wide range of ecosystems, including wetlands, estuaries, coastal zones, lakes, forests, marine ecosystems, lagoons, agricultural systems, landscapes, and rivers. The text synthesizes material from a variety of books, journals, and private research, to consider biodiversity, energy needs, ecological economics, and natural capital in the measurement of ecological health. Organized for ease of reference, the first part of the handbook provides the required theoretical background. It presents a complete overview of all relevant ecological indicators - including thermodynamics, resilience estimates, exergy, and emergy indicators. The second part focuses on how to effectively apply the ecological indicators to a number of important ecosystems. It includes many examples and case studies that clearly illustrate the advantages and disadvantages of each method for specific applications. Offering first-hand insight and practical guidance from practitioners in the field, this complete resource supplies the tools and the well-rounded understanding required to diagnose the health of virtually any ecosystem with much improved accuracy.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Ecosystem health; Environmental indicators